2018
DOI: 10.1007/978-1-4939-7565-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of p16 Promoter Hypermethylation by Methylation-Specific PCR

Abstract: DNA methylation plays a decisive role in the regulation and control of gene expression. DNA methylation is a covalent modification, in which a methyl group is attached to the 5th carbon of the cytosine ring of a CpG dinucleotide that is located upstream from the promoter region of a gene. Promoter hypermethylation (gain of DNA methylation) of the p16 gene may cause silencing of gene expression and plays an important role in cancer. Therefore, detection of the methylation status of p16 gene is an important tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As an endpoint analysis technique[40], the primary limitation of MSP is that it yields qualitative results, meaning that well-standardized MSP assays provide information that is restricted to the presence of methylated, unmethylated, or both methylated and unmethylated alleles[41].…”
Section: Resultsmentioning
confidence: 99%
“…As an endpoint analysis technique[40], the primary limitation of MSP is that it yields qualitative results, meaning that well-standardized MSP assays provide information that is restricted to the presence of methylated, unmethylated, or both methylated and unmethylated alleles[41].…”
Section: Resultsmentioning
confidence: 99%
“…We further explored the potential mechanism of GABRP overexpression in pancreatic cancer from the perspective of epigenetics. DNA methylation plays an important role in regulating gene expression and aberrant DNA methylation is involved in cancer progression ( 45 ). DNA hypomethylation is frequently observed in human tumors and contributes to the aberrant activation of specific genes related to cancer progression ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of p16 gene hypermethylation is often used as a biomarker for the early diagnosis and prognosis of HNSCC (Figure 2). Methylation‐specific polymerase chain reaction (MSP) and other molecular techniques are commonly employed to assess the methylation status of the p16 gene in tumor samples 42 . The presence of p16 hypermethylation may indicate an increased risk of HNSCC, and also it can act as a potential therapeutic target 38 .…”
Section: Diagnosis In Personalized Medicinementioning
confidence: 99%
“…Methylation‐specific polymerase chain reaction (MSP) and other molecular techniques are commonly employed to assess the methylation status of the p16 gene in tumor samples. 42 The presence of p16 hypermethylation may indicate an increased risk of HNSCC, and also it can act as a potential therapeutic target. 38 Research has shown that the methylation status of the DAPK gene promoter is altered in HNSCC and is associated to its progression, prognosis, and response to therapy.…”
Section: Diagnosis In Personalized Medicinementioning
confidence: 99%